STORY TELLING KEARIFAN LOKAL JAWA TIMUR BERBASIS DIGITAL DALAM PENANAMAN NILAI PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Moh. Farid Nurul Anwar; Antonius Alam Wicaksono (Universitas Tribhuwana Tunggadewi, 2026)
This study addresses the limited familiarity of elementary students with local folktales and the predominantly textual and less engaging character education practices in schools. Folktales, however, embody essential moral values such as responsibility, honesty, cooperation, and courage, which are important to instill from an early age. The purpose of this research is to develop a digital storytelling medium based on East Javanese local wisdom that is valid and effective in fostering character education values among elementary school students. The study adopts a Research and Development (RD) design using the Borg and Gall model, implemented through nine stages from preliminary study to field trials. Data were collected through observation, interviews, expert validation questionnaires, and student learning achievement tests. Quantitative descriptive analysis was applied to calculate expert validation scores, student learning outcomes, and character improvement using the N-gain formula. The developed medium, containing four East Javanese folktales (Joko Tole, Ande-Ande Lumut, Roro Anteng and Joko Seger, and Sura and Baya), obtained an average validity score of 89%, categorized as highly valid. Small group and field trials demonstrated that the medium successfully increased student engagement, improved material comprehension, and enhanced learning outcomes with an average mastery of 91.50%. In addition, students’ character values (responsibility, honesty, cooperation, and courage) improved, achieving an N-gain score of 0.72 in the high category. In conclusion, the digital storytelling medium based on East Javanese local wisdom is both valid and effective, making it a promising tool for strengthening the internalization of character education in elementary schools.